Exploring bilingual cognition in younger and older adults and second language learners - Connolly, Anne-Marie (Trinity College (Dublin, Ireland). School of Psychology, 2017)
There is extensive research investigating the benefits of bilingualism on the ways that basic cognitive abilities develop, function and change throughout the lifespan, particularly from cohorts at either end of the developmental lifespan. The central aspect of the bilingual experience that gives rise to generalised effects on cognitive function comes from the well-documented finding that both languages of the bilingual are jointly active, even in situations where only one language is required. Joint activation produces the processing problem of selecting, attending to and maintaining the target language and inhibiting the non-target language. To manage this conflict the domain-general executive control system is recruited, and through its sustained and persistant exercise it is strengthened.
Keywords: Psychology, Ph.D.; PhD Trinity College Dublin, 2017